Synthesis of Monoazo Reactive Dyes Based on 2-(3’-Chlorostyryl)-6-Amino-4-Oxoquinazoline System and Their Application - Shukla, J.N.; A. Desai, Vikas; Desai, K.R. (Asian Journal of Chemistry, 2010)
2-( 1´-Hydroxy naphthyl-3´-monosulphonic acid-6´-yl-amino)-4- (2"-meta-chloro-styryl-4"-oxoquinazoline-6"-yl-amino )-6-chloro-S- triazine used as coupling component was synthesised by treatment of 2-( l´-hydroxy naphthyl-3´-monosulphonic acid-6´ -yl-amino)-4,6- dichloro-S-triazine with 2-(3´-chloro-styryl)-6-amino-4-oxoquinazoline was coupled with diazo solutions of various amines to give 2-(1´-hydroxy-2´-azo-naphthyl-3´monosulphonic acid-6´-yl-amino )-4-(2" -meta-chloro-styryl-4"-oxoquinazoline-6"-yl-amino) -6-chloro-S-triazine. Coupling component was prepared by dissolving a mixture of J-acid and cyanuric chloride. Dyeing properties of these dyes on cotton, wool and silk were assessed. A study of the fastness of dyed patterns showed that dyes had good light fastness, good to excellent fastness to washing and rubbing and very good to excellent exhaustion.